Curvivirga aplysinae gen. nov., sp. nov., a marine bacterium isolated from the sea sponge Aplysina fistularis. Issue 7 (6th July 2021) - Goldberg, Stacey R.; Haltli, Brad A.; Correa, Hebelin; Kerr, Russell G.
Abstract : A Gram-stain-negative, strictly aerobic, motile bacterium, designated strain RKSG073 T, was isolated from the sea sponge Aplysina fistularis, collected off the west coast of San Salvador, The Bahamas. Cells were curved-to-spiral rods with single, bipolar (amphitrichous) flagella, oxidase- and catalase-positive, non-nitrate-reducing and required salt for growth. RKSG073 T grew optimally at 30–37 °C, pH 6–7, and with 2–3 % (w/v) NaCl. The predominant fatty acids of RKSG073 T were summed feature 8 (C18 : 1 ω6 c and/or C18 : 1 ω7 c ) and C16 : 0 . Major isoprenoid quinones were identified as Q-10 and Q-9. Phylogenetic analyses of nearly complete 16S rRNA genes and genome sequences positioned strain RKSG073 T in a clade with its closest relative Aestuariispira insulae AH-MY2 T (92.1 % 16S rRNA gene sequence similarity), which subsequently clustered with Hwanghaeella grinnelliae Gri0909 T, Marivibrio halodurans ZC80 T and type species of the genera Kiloniella, Thalassospira and Terasakiella . The DNA G+C content calculated from the genome of RKSG073 T was 42.2 mol%. On the basis of phylogenetic distinctiveness and polyphasic analysis, here we propose that RKSG073 T (culture deposit numbers: ATCC collection = TSD-74 T, BCCM collection = LMG 29869 T ) represents the type strain of a novel genus and species within the family Kiloniellaceae, order Rhodospirillales and class Alphaproteobacteria, for which the name Curvivirga aplysinae gen. nov., sp. nov. is proposed.